A survey of eyecare affordability among patients seen in collaborative care in Australia and factors contributing to cost barriers - Rene Cheung; Angelica Ly (Sax Institute, 2024)
Aim: The decline in the real value of rebates from Australia's national public health insurance scheme, Medicare, over the past decade has contributed to increased out-of-pocket costs for eyecare services, which threatens affordability. This study measured eyecare affordability and cost barriers among patients seen in collaborative care. Methods: We conducted a cross-sectional survey of 252 patients who had attended a collaborative eyecare clinic in the previous year. A modified affordability subscale was used to measure eyecare and general healthcare affordability. Two population scores were calculated: the average percentage of patients experiencing cost barriers (mean of the five item percentages for general healthcare, and optometric and specialist eyecare), and the proportion indicating one or more cost barriers. Factors associated with eyecare and general healthcare affordability were identified using linear regression. Results: The response rate was 46.8% (n = 118/252). The mean percentage of patients not obtaining services because of cost ranged from 23.4% (standard deviation [SD] 8.8) for general healthcare to 25.5% (SD 6.3) for specialist eyecare. Direct or indirect cost barriers to one or more services were experienced by 45.2% (n = 52/115) of respondents for optometric eyecare and 40.4% (n = 44/109) for specialist eyecare. Services not covered by private health insurance or Medicare (for example, out-of-pocket dental and optical) were ranked the most difficult to afford. Poorer self-rated health (p = 0.004, β = 0.293) and the lack of private hospital health insurance (p = 0.014, β = 0.249) were associated with reduced optometric eyecare affordability. This was also true for specialist eyecare affordability (self-rated health p = 0.002, β = 0.306; private hospital health insurance p = 0.004, β = 0.286). A lack of private hospital health insurance (p = 0.001, β = 0.312), younger age (p < 0.001, β = -0.418) and holding a concession card (p = 0.011, β = 0.272) were all associated with reduced affordability of general healthcare. Conclusion: A high proportion of patients seen in collaborative care experience cost barriers to accessing eyecare, particularly for services not covered by private health insurance or Medicare. These findings indicate that affordability concerns exist despite significant reductions in the direct cost of services within a collaborative care setting. They also provide insights on the subpopulations most vulnerable to rising eyecare costs.